2021
DOI: 10.3390/educsci11010032
|View full text |Cite
|
Sign up to set email alerts
|

When Authenticity Goes Missing: How Monocultural Children’s Literature Is Silencing the Voices and Contributing to Invisibility of Children from Minority Backgrounds

Abstract: The importance of recognising, valuing and respecting a child’s family, culture, language and values is central to socially just education and is increasingly articulated in educational policy worldwide. Inclusive children’s literature can support children’s human rights and contribute to equitable and socially just outcomes for all children. However, evidence suggests many educational settings provide monocultural book collections which are counterproductive to principles of diversity and social justice. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Importantly, evidence also shows even very young children are more than capable of, and open to, having such discussions. However, many educators, including those in this study, are fearful of 'getting it wrong' or not being 'politically correct' (Adam, 2021) and this contributes to the avoidance of conversations about race or racism and instead leads to a focus on the exotic or other. Further, this uncertainty may have been the key to educators' approach and foci evident in the following four themes.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Importantly, evidence also shows even very young children are more than capable of, and open to, having such discussions. However, many educators, including those in this study, are fearful of 'getting it wrong' or not being 'politically correct' (Adam, 2021) and this contributes to the avoidance of conversations about race or racism and instead leads to a focus on the exotic or other. Further, this uncertainty may have been the key to educators' approach and foci evident in the following four themes.…”
Section: Discussionmentioning
confidence: 94%
“…However, educators from all centres except Dockside expressed concerns about not knowing what was "politically correct"' when choosing or sharing diverse books with children. Some saw attention to diversity as mainly relating to linguistic diversity and the authors note this aspect of the study has been focused on in another paper (Adam, 2021) When educators described how they enacted book sharing to address or acknowledge diversity, they mostly referred to focusing on celebrations, or the "different" or "special" aspects of "other" cultures. Educators exhibited a noticeably high level of con dence when talking about this which contrasted noticeably with their hesitation and uncertainty when they described how they respond to children's In each of the four sessions in which the educators focused on cultural diversity, educator practice focused on cultural diversity as special or other.…”
Section: Book Sharing Contextsmentioning
confidence: 99%
“…Finding primary grade level books written by a multicultural set of authors that center on in‐depth social issues and promote a call to action was difficult for us because local libraries were somewhat limited, and children's books often oversimplify social issues typically centering on individual behavior and passive activism (Echterling, 2016). “Evidence suggests many educational settings provide monocultural book collections which are counterproductive to principles of diversity and social justice” (Adam, 2021, p. 1). As Echterling (2016) posits, in order to “make real, lasting differences,” (p. 294), children's literature should do more to encourage civic engagement by showcasing the systemic problems around issues.…”
Section: Discussionmentioning
confidence: 99%
“…Yoo‐Lee et al (2014) suggested that cultural authenticity comprises accurate details and perspectives of an ethnic group in text and illustrations without stereotypes. Other researchers (Adam, 2021; Southard et al, 2014) maintained that culturally authentic literature should also develop a sense of identity, self‐esteem, and openness for cultural diversity. Wee et al (2014) contended that “the key to accurately representing Asian American cultures in children's literature is to first recognize the diversity of Asian peoples” (p. 72).…”
Section: Introductionmentioning
confidence: 99%